Refractive Precision of Ray Tracing IOL Calculations Based on OCT Data versus Traditional IOL Calculation Formulas Based on Reflectometry in Patients with a History of Laser Vision Correction for Myopia - Gjerdrum B (Dove Medical Press, 2021)
Bjørn Gjerdrum,1,2 Kjell Gunnar Gundersen,2 Per Olof Lundmark,1 Bente Monica Aakre1 1Department of Optometry, Radiography and Lighting Design, University of South-Eastern Norway, Kongsberg, Norway; 2Ifocus Eye Clinic, Haugesund, NorwayCorrespondence: Bjørn Gjerdrum Brønngata 36, Stavanger, 4008, NorwayTel +47 415 11 935Email bjorn@ifocus.noPurpose: To compare the refractive predictability of ray tracing IOL calculations based on OCT data versus traditional IOL calculation formulas based on reflectometry in patients with a history of previous myopic laser vision correction (LVC).Patients and Methods: This was a prospective interventional single-arm study of IOL calculations for cataract and refractive lens exchange (RLE) patients with a history of myopic LVC. Preoperative biometric data were collected using an optical low coherence reflectometry (OLCR) device (Haag-Streit Lenstar 900) and two optical coherence tomography (OCT) devices (Tomey Casia SS-1000 and Heidelberg Engineering Anterion). Traditional post LVC formulas (Barret True-K no-history and Haigis-L) with reflectometry data, and ray tracing IOL calculation software (OKULIX, Panopsis GmbH, Mainz, Germany) with OCT data were used to calculate IOL power. Follow-up examination was 2 to 3 months after surgery. The main outcome measure, refractive prediction error (RPE), was calculated as the achieved postoperative refraction minus the predicted refraction.Results: We found that the best ray tracing combination (Anterion-OKULIX) resulted in an arithmetic prediction error statistically significantly lower than that achieved with the best formula calculation (Barret True-K no-history) (− 0.13 D and − 0.32 D, respectively, adjusted p = 0.01), while the Barret TK NH had the lowest SD. The absolute prediction error was 0.26 D and 0.35 D for Anterion-OKULIX and Barret TK NH, respectively, but this was not statistically significantly different. The Anterion-OKULIX calculation also had the highest percentage of eyes within ± 0.25, compared to both formulas and within ± 0.50 and ± 0.75 compared to the Haigis-L (p = 0.03).Conclusion: Ray tracing calculation based on OCT data from the Anterion device can yield similar or better results than traditional post LVC formulas. Ray tracing calculations are based on individual measurements and do not rely on the ocular history of the patient and are therefore applicable for any patient, also without previous refractive surgery.Keywords: post-LVC, OCT, ray tracing, IOL calculation, biometry, individual calculation, prediction error